A variable-weather-parameter MPPT method based on a defined characteristic resistance of photovoltaic cell. (15th March 2020) - Li, Shaowu; Ping, Aihong; Liu, Yefeng; Ma, Xiaohong; Li, Chao
Highlights: A VWP MPPT method based on a defined characteristic resistance of PV cell is proposed. The MPPT constraint conditions based on this characteristic resistance are found. The direct relationship between V oc, I sc, R L and control signal at the MPP is built. The contradiction between MPPT performance and algorithm complexity is resolved well. The rapidity and accuracy are improved by 82.176% and 1.876% over P&O method, respectively. Abstract: A characteristic resistance of photovoltaic (PV) cell is defined in this paper to find the mathematical equation of the control signal at the maximum power point (MPP) and to obtain the maximum power point tracking (MPPT) constraint conditions. Based on it, a variable-weather-parameter (VWP) MPPT method is proposed. The major purpose is to greatly improve the MPPT speed and make the design of PV system more convenient. By this method, the real-time value of the control signal at the MPP can be directly calculated. Meanwhile, the topology of PV system can be conveniently selected by the proposed MPPT constraint conditions. Finally, some simulations whose models are built by MATLAB software are done. Results show that the proposed MPPT constraint conditions is accurate regardless of the solar irradiance or temperature, verify that the proposed method is feasible, available and accurate to track the MPP successfully, and illustrate that there is a better MPPT performance than the perturbation and observation (P&O) method under fast changing weather conditions.